Successful treatment of non‐Hodgkin lymphoma associated immune thrombocytopenia with involved field radiotherapy. Issue 4 (22nd April 2013) - Berrang, Tanya; Holloway, Caroline; Hart, Jason; Yee, Adrian; Berry, Brian; Kotb, Rami
Abstract Immune thrombocytopenia complicates the course and impacts the outcome of non‐Hodgkin lymphoma (NHL‐ITP, non‐Hodgkin lymphoma–immune thrombocytopenic purpura). The response to corticosteroids and/or intravenous immune globulins is usually short lasting, but NHL‐ITP usually responds to anti‐lymphoma chemotherapy. It is not clear if this success is due to the elimination of the lymphomatous tissue or to the immunosuppressor/immunomodulator effect of chemotherapy. Myelosuppressive anti‐lymphoma chemotherapy carries the risk of severe thrombocytopenia that may not respond adequately to platelet transfusion support. We report on a patient with recurrent diffuse large B‐cell lymphoma that coincided with immune thrombocytopenia. Both diseases completely responded to involved field radiation therapy. This supports the hypothesis that at least in some cases of NHL‐ITP, the lymphomatous clone secretes the anti‐platelet antibodies. This supports the therapeutic decision making for these patients. Copyright © 2013 John Wiley & Sons, Ltd.